Ethical Aspects of Blood Donors and the Recipients of Their Blood. (19th January 2012) - van den Burg, P. J. M.; Magnussen, K.
Abstract : To date medical care is inextricable based on blood donors and blood products. The continuing increase and intensification of tests and guidelines also results in a change in deferral and abnormal test results. Donors and recipients of their blood are faced with this information and are confronted with a kaleidoscope of thoughts and emotions. The discussion with respect to paid versus nonpaid donation is not new, but other aspects are less often discussed. We describe these other aspects for donors and recipients of their blood and hope to open the ethical discussion; if and to what extent we should have limits?